Factors of unemployment rate in Malaysia / Nur Najihah Mat Zain - Mat Zain, Nur Najihah (Faculty of Business and Management, 2019)
The issue of Unemployment Rate in Malaysia is very current issue nowadays. The objective of this study is to evaluate the relationship between Unemployment Rate (UR) with FDI, INF, GDP and POP In this study, Unemployment Rate (UR) is the dependent variable while the macroeconomic factors are independent variables. The time period observed is from the year 1970 to the year 2017 and all the tests will be conducted based on annually data which is total 48 observations. The Multiple Regression Analysis method is used as the analysis procedure predicting the Unemployment Rate (UR). The result of this study shows that the independent variable of Inflation Rate (INF) and POP are negative significantly with Unemployment Rate (UR). For GDP is positive significant result with Unemployment Rate (UR). FDI is negative insignificant with Unemployment Rate (UR). Investors and government should consider these variables in order to detect early sign of unemployment rate in Malaysia thus can take some initiatives to prevent these problems.